Youth Pathways in Articulated Postsecondary Systems: Enrolment and Completion Patterns of Urban Young Women and Men - Andres, Lesley; Krahn, Harvey (Canadian Journal of Higher Education, 1999)
This paper uses panel survey data to document the postsecondary educational activity of high school graduates in Edmonton and Vancouver over a five-year period. It enquires whether, in "articulated" postsecondary systems offering a range of institutional choices and a variety of transfer options, large class and gender differences in participation and completion continue to be observed. The results reveal that even in systems explicitly designed to improve access to and encourage completion of postsecondary programs, family background continues to strongly influence postsecondary outcomes. In both cities, social class advantages appear to be passed from one generation to the next, to a large extent, through the high school tracking system, since high school academic program is a strong predictor of postsecondary participation and completion. Gender also continues to matter, but in more subtle ways than in the past.